2016
DOI: 10.1016/j.jmii.2011.12.019
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between levofloxacin consumption and the incidence of nosocomial infections due to fluoroquinolone-resistant Escherichia coli

Abstract: There is a significant correlation between levofloxacin use and the incidence of nosocomial fluoroquinolone-resistant E coli isolates. The incidence of fluoroquinolone-resistant E coli could be reduced by limiting levofloxacin consumption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 24 publications
3
25
0
2
Order By: Relevance
“…In accordance with previous studies, our results found that the FQR E. coli was significantly associated with FQs consumption [9][10][11][12][13][14][15][16][17][18] . The most important resistance mechanism of E. coli to quinolones is mutation of target gene DNA gyrase and topoisomerase IV.…”
Section: Correlation Between Antibiotics Consumption Intensity and Fqrsupporting
confidence: 93%
“…In accordance with previous studies, our results found that the FQR E. coli was significantly associated with FQs consumption [9][10][11][12][13][14][15][16][17][18] . The most important resistance mechanism of E. coli to quinolones is mutation of target gene DNA gyrase and topoisomerase IV.…”
Section: Correlation Between Antibiotics Consumption Intensity and Fqrsupporting
confidence: 93%
“…However, the correlation of ciprofloxacin-resistant A. baumannii and the antibiotics consumption was not found. Consistant with previous studies, our results found that the FQR E. coli was significantly associated with FQs consumption [10][11][12][13][14][15][16][17][18][19]. The most important resistance mechanism of E. coli to quinolones is mutation of target gene DNA gyrase and topoisomerase IV.…”
Section: Discussionsupporting
confidence: 69%
“…When considering fluoroquinolones and E. coli specifically, few studies have evaluated the impact of a quinolone restriction on E. coli susceptibility, and only one such study evaluated the impact of a quinolone restriction on E. coli urinary isolates . In that study, the authors reported the impact of a nationwide restriction of ciprofloxacin on resistance patterns of E. coli urinary isolates.…”
Section: Discussionmentioning
confidence: 99%